2020
DOI: 10.3847/2041-8213/ab7341
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Electrons Observed Down to <7 keV in a NuSTAR Solar Microflare

Abstract: We report the detection of emission from a nonthermal electron distribution in a small solar microflare (GOES class A5.7) observed by the Nuclear Spectroscopic Telescope Array, with supporting observation by the Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI). The flaring plasma is well accounted for by a thicktarget model of accelerated electrons collisionally thermalizing within the loop, akin to the "coronal thick-target" behavior occasionally observed in larger flares. This is the first posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 32 publications
15
71
2
Order By: Relevance
“…The largest upper limit obtained from this analysis (∼10 25 erg s −1 ) is only just comparable to the smallest nonthermal power in similar sized microflares (Hannah et al 2008, Table 1). The power-law index and cut-off energy are consistent with the values obtained in Glesener et al (2020). Only the electron flux is different (∼10 3 larger), which could be expected as the peak emission is also orders of magnitude larger than the flare discussed here.…”
Section: Non-thermal Limitssupporting
confidence: 89%
See 2 more Smart Citations
“…The largest upper limit obtained from this analysis (∼10 25 erg s −1 ) is only just comparable to the smallest nonthermal power in similar sized microflares (Hannah et al 2008, Table 1). The power-law index and cut-off energy are consistent with the values obtained in Glesener et al (2020). Only the electron flux is different (∼10 3 larger), which could be expected as the peak emission is also orders of magnitude larger than the flare discussed here.…”
Section: Non-thermal Limitssupporting
confidence: 89%
“…Since the first solar NuSTAR observations in 2014 (see Grefenstette et al 2016;Hannah et al 2016;Kuhar et al 2017), solar activity has decreased allowing sub-A class microflares to be observed regularly within ARs (Glesener et al 2017(Glesener et al , 2020Wright et al 2017;Hannah et al 2019) and small brightenings outside of ARs (Kuhar et al 2018). 8 The AR microflares observed by NuSTAR have been found to have thermal energy releases down to 10 27 erg with quiet Sun brightenings having energies down to 10 26 erg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microflare aug1850, which was confirmed to involve significant nonthermal emission in Glesener et al (2020), is the only event to show behavior consistent with the Neupert effect with the use of this method. Specifically, the AIA derivative is best correlated with both the NuSTAR 6-8 and 8-10 keV time profiles when no lag is applied at all (see bottom panel of Figure 6).…”
Section: Neupert Effectmentioning
confidence: 78%
“…One considers an A1-class microflare that is the first observed by both NuSTAR and the Interface Region Imaging Spectrograph (IRIS), making it the first event at this scale where HXR coronal emission has been compared with corresponding cooler chromospheric UV emission as seen by IRIS (Hannah et al 2019). The other presents a GOES A7.7 8 event that is the first NuSTAR microflare to show clear evidence of nonthermal emission (Glesener et al 2020). This last event occurred alongside several other microflares during a 2017 August 21 NuSTAR observation and is also discussed in this paper.…”
Section: Nustar Solar Observationmentioning
confidence: 99%